EXPLORING CODE-SWITCHING AS A COMMUNICATION TOOL IN ORANGUTAN TOURS: A STUDY OF BUKIT LAWANG TOUR GUIDES - Siti Aisyah (SUAN PUBLISHER, 2025)
The aimed of this study was to examine the various types of code-switching used by tour guides during their interactions with visitors on Orangutan tours in Bukit Lawang. The focused of the study was on how code-switching functions as an essential communication tool in facilitating understanding and connection between the guides and their multilingual audiences. Specifically, the study sought to identify instances of code-switching in the tour guides' spoken interactions, categorized these occurrences based on established linguistic classifications, and determine which type of code-switching appears most frequently.This research was conducted by utilized qualitative method with descriptive approach. The data for this study were gathered through conversations that took place between tour guides and tourists during Orangutan Tours in Bukit Lawang. These interactions were observed and recorded using audio equipment to capture authentic language use in real-time settings. The findings of this study revealed the presence of three distinct types of code-switching used by the tour guide during interactions with tourists. These types were: inter-sentential switching, intra-sentential switching, and tag switching. In total, the study identified 12 instances of code-switching, each categorized under one of the three types. Specifically, there were 2 instances of tag switching, 5 instances of inter-sentential switching, and 5 instances of intra-sentential switching.